Didactic poetry of Greece, Rome and beyond knowledge, power, tradition - Canevaro, Lilah Grace; O'Rourke, Donncha (Swansea : The Classical Press of Wales, 2019)
Here a team of established scholars offers new perspectives on poetic texts of wisdom, learning and teaching related to the great line of Greek and Latin poems descended from Hesiod. In previous scholarship, a drive to classify Greek and Latin didactic poetry has engaged with the near-total absence in ancient literary criticism of explicit discussion of didactic as a discrete genre. The present volume approaches didactic poetry from different perspectives: the diachronic, mapping the development of didactic through changing social and political landscapes (from Homer and Hesiod to Neo-Latin didactic); and the comparative, setting the Graeco-Roman tradition against a wider backdrop (including ancient near-eastern and contemporary African traditions). The issues raised include knowledge in its relation to power; the cognitive strategies of the didactic text; ethics and poetics; the interplay of obscurity and clarity, playfulness and solemnity; the authority of the teacher.
Introduction / Lilah Grace Canevaro and Donncha O'Rourke -- Part I. Theory. -- Knowledge is power: dynamics of (dis)empowerment in didactic poetry / Donncha O'Rourke -- Thinking for yoursel: Hesiod's Works and days and cognitive training / Lilah Grace Canevaro -- Part II. Tracing tradition. -- Homer Ethicus / David Sider -- Elegiac pharmacology: the didactic heirs of Nicander? / Floris Overduin -- Name puns and acrostics in didactic poetry: reading the universe / Monica R. Gale -- Part III. Comparisons and continuations. -- DIdactic and apocalyptic turns: clarity and obscurity, Homer and Hesiod in the Sibylline oracles / Helen Van Noorden -- Embodied teaching: Ludlul Bēl Nēmeqi and the Babylonian didactic tradition / Johannes Haubold -- Fauna and erotic didactics in archaic Greek and Kalanga oral wisdom literatures / Madhlozi Moyo -- Scientia demands the Latin muse: the authority of didactic poetry in early-modern Scotland / David McOmish.
JSTOR
Keywords: Didactic poetry, Classical -- History and criticism; Poésie didactique ancienne -- Histoire et critique; Poetry; LITERARY CRITICISM; Didactic poetry, Classical; Electronic books; Criticism, interpretation, etc